2020
DOI: 10.18280/mmep.070203
|View full text |Cite
|
Sign up to set email alerts
|

Variable Temperature and Concentration Impacts on Radiative Chemically Magnetohydrodynamic Viscoelastic Fluid Flow Through Porous Moving Plate

Abstract: The flow has been made by considering variable temperature and radiation effects for the magnetohydrodynamic viscoelastic fluid past a moving vertical plate in a porous medium. Chemical reaction and concentration have been taken into account. The governed mathematical statement is handled analytically by perturbation technique. The main view of this research is to investigate the effects of parameters and numbers in the problem on fluid flow, thermal boundary and concentration profiles. The velocity profile ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[26][27][28][29]. Several research studies on undermining numerical solutions of unsteady MHD flow heat transfer over a stretching surface with suction or injection are interpreted in miscellaneous research articles [30][31][32][33][34][35][36][37][38][39]. Keeping in view all the above facts a novel problem has been presented and solved.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29]. Several research studies on undermining numerical solutions of unsteady MHD flow heat transfer over a stretching surface with suction or injection are interpreted in miscellaneous research articles [30][31][32][33][34][35][36][37][38][39]. Keeping in view all the above facts a novel problem has been presented and solved.…”
Section: Introductionmentioning
confidence: 99%
“…Varying the concentration with temperature impact on MHD radiative chemically viscoelastic liquid flow on a vertical plate. Suneetha et al 3,4 and Raju et al 5 elucidate the stagnant motion of Casson liquid with induced magnetic field alongside homogeneous and heterogeneous reactions. Their findings revealed that the performance of heat transport in Newtonian liquids was high as compared to non-Newtonian liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Rajput et al 25–27 studied the flow over an impulsively started vertical plate embedded in a porous matrix. Mass and heat transfer analysis of a viscoelastic fluid was studied by Kumaresan and colleagues 28–31 . Recently, Rajakumar et al 32 examined the Dufour effects on unsteady flow past an impulsively started infinite vertical plate in a porous medium using Walters Bfalse′ $B^{\prime} $ model.…”
Section: Introductionmentioning
confidence: 99%